Airway epithelial cell expression of interleukin-6 in transgenic mice. Uncoupling of airway inflammation and bronchial hyperreactivity. - DiCosmo, B F; Geba, G P; Picarella, D; Elias, J A; Rankin, J A; Stripp, B R; Whitsett, J A; Flavell, R A (The Journal of Clinical Investigation, 1994)
We produced transgenic mice which overexpress human IL-6 in the airway epithelial cells. Transgenic mice develop a mononuclear cell infiltrate adjacent to large and mid-sized airways. Immunohistochemistry reveals these cells to be predominantly CD4+ cells, MHC class II+ cells, and B220+ cells. Transgenic mice and nontransgenic mice had similar baseline respiratory system resistance (0.47 +/- 0.06 vs 0.43 +/- 0.04 cmH2O/ml per s at 9 wk of age, P = NS and 0.45 +/- 0.07 vs 0.43 +/- 0.09 cmH2O/ml per s at 17 wk of age, P = NS). Transgenic mice, however, required a significantly higher log dose of methacholine to produce a 100% increase in respiratory system resistance as compared with non-transgenic littermates (1.34 +/- 0.24 vs 0.34 +/- 0.05 mg/ml, P < or = 0.01). We conclude that the expression of human IL-6 in the airways of transgenic mice results in a CD4+, MHC class II+, B220+ lymphocytic infiltrate surrounding large and mid-sized airways that does not alter basal respiratory resistance, but does diminish airway reactivity to methacholine. These findings demonstrate an uncoupling of IL-6-induced airway lymphocytic inflammation and airway hyperresponsiveness and suggest that some forms of airway inflammation may serve to restore altered airway physiology. Images